2021
DOI: 10.1155/2021/5539349
|View full text |Cite
|
Sign up to set email alerts
|

“Primary Hyperparathyroidism (PHPT) in Children: Two Case Reports and Review of the Literature”

Abstract: Primary hyperparathyroidism (PHPT) is a rare disorder in children and adolescents. Typical biochemical features are hypercalcemia and hypophosphatemia, but the clinical features can be heterogeneous, and in some cases, symptoms are vague and nonspecific, leading to misdiagnosis or late diagnosis. Herein, we report two cases of PHPT in pediatric age with different presenting symptoms, pain in the foot, and progressive alteration of the gait in the first case and recurrent abdominal pain with emotional lability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…PHPT can manifest with a variety of symptoms involving the gastrointestinal, musculoskeletal, renal and neurological systems, and at the onset of the disease, about 80% of children are found to have end organ damage, mainly bone and kidney. 7 Failure to measure at least the Ca concentration at the first signs of the disease may lead to inadequate and delayed diagnosis of the underlying disease and development of the symptomatic form, which may ultimately result in irreversible target organ involvement: bone destruction, urolithiasis, destruction of the urinary system secondary to urolithiasis, pancreatitis or gastric ulcer disease. 3 In addition to the well-known skeletal symptoms, PHPT can cause especially during growth spurt rare skeletal deformities such as genu valgum, subluxation of upper femoral epiphysis (SUFE) and epiphyseal displacement.…”
Section: Discussionmentioning
confidence: 99%
“…PHPT can manifest with a variety of symptoms involving the gastrointestinal, musculoskeletal, renal and neurological systems, and at the onset of the disease, about 80% of children are found to have end organ damage, mainly bone and kidney. 7 Failure to measure at least the Ca concentration at the first signs of the disease may lead to inadequate and delayed diagnosis of the underlying disease and development of the symptomatic form, which may ultimately result in irreversible target organ involvement: bone destruction, urolithiasis, destruction of the urinary system secondary to urolithiasis, pancreatitis or gastric ulcer disease. 3 In addition to the well-known skeletal symptoms, PHPT can cause especially during growth spurt rare skeletal deformities such as genu valgum, subluxation of upper femoral epiphysis (SUFE) and epiphyseal displacement.…”
Section: Discussionmentioning
confidence: 99%
“…Hypercalcemia in children and adolescents can present with gastrointestinal symptoms (anorexia, vomiting, abdominal pain, or constipation), neurological manifestations (drowsiness, dizziness, irritability, confusion, lethargy, and seizures), cardiac concerns (hypertension or arrhythmias), and renal complications (nephrocalcinosis, nephrolithiasis, or hematuria). [1][2][3][4] Once elevated serum calcium levels are found, it is important to determine the etiology. In this patient's case, there was a significant elevation in PTH levels, making primary hyperparathyroidism the most likely cause.…”
Section: Discussionmentioning
confidence: 99%
“…3 However, with this disease process, a defect in the parathyroid gland results in excessive PTH secretion despite high calcium levels, as the calcium sensing receptor (CaSR) gene has a mutation. 5,6 The majority of cases are due to parathyroid adenomas (roughly 90%), 1,4,6 although parathyroid hyperplasia can occur in approximately 10% of cases, and parathyroid carcinoma, although possible, is quite rare, found only in less than 1% of cases. 6 Primary hyperparathyroidism in children and adolescents is relatively uncommon, consisting of less than 5% of all cases.…”
Section: Discussionmentioning
confidence: 99%
“…In pediatrics, data are scarce, and to our knowledge, only 50 pediatric patients (including the 18 patients presented here) out of a total of almost 1,200 pediatric patients reported in the literature with PHPT, have been treated with cinacalcet, as summarized in Table 4 ( 15 , 16 , 21 25 , 27 30 , 32 , 33 , 35 37 , 40 , 43 45 ). The present study almost doubles the number of reported pediatric patients having received cinacalcet as an off-label drug for PHPT.…”
Section: Discussionmentioning
confidence: 99%
“…Cinacalcet was recently licensed in Europe in dialysis children above 3 years with secondary hyperparathyroidism due to end-stage kidney disease; European guidelines have delineated its use in this peculiar setting ( 14 ). Alternatively, the use of cinacalcet, as an off-label therapy in PHPT, has been reported only in few pediatric case reports and is considered to be a challenge in daily practice, because of the putative risk of hypocalcemia, increased QT interval and drug interactions ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%